Beyond Smell-O-Vision: Possibilities for Smell-Based Digital Media. (August 2017) - Olofsson, Jonas K.; Niedenthal, Simon; Ehrndal, Marie; Zakrzewska, Marta; Wartel, Andreas; Larsson, Maria
Research Problem: The purpose of this research synthesis is to identify new opportunities for smell-enabled games based upon currentolfactory research, and to present early game concepts that have emerged from our empirical assessments. Literature Review: We briefly summarize key projects in the history ofscent technologies for film and media. Human-Computer Interaction researchers have also explored a number of uses for scent delivery in interactive digital media. Recent developments in olfactory psychology and neuroscience research suggest that a fruitful avenue for exploration is to developlearning games that expand olfactory capacity. Methodology: We have conducted two studies of computer-based perceptual and cognitive olfactory tasks. Mixture perception experiment: We designed a perceptual experiment where the task was to correctly estimate the intensity of odor components in a blend of coffee and tea. Blended odors were presented to 10 healthy adults by means of a computer-controlled olfactometer. Following each stimulation, the participant used a computer interface to estimate the intensity of components of the blend. Event-based memory experiment: We have developed a digital olfactory version of the children's game "Memory." The game interface consists of 32 white squares that are presented in a grid pattern on the screen and that, when participants click on them, triggers the release of one of eight possible smells from the olfactometer. Fifteen healthy adult participants were tested in 10 laboratory sessions distributed over three weeks. Results and Conclusions: Our empirical results suggest thatsmell training through learning games holds promise as a means of improving cognitive function. The results of our event-based memory experiment suggest that both olfactory and visual memory capacities might have benefitted from olfactory game training. The results of our mixture perception experiment indicate that binary odor mixtures might provide a suitable starting point for perceptual training, and we suggest that a smell-enabled game might include adaptive difficulty by progressively introducing more complex mixtures. We have used event-based memory and mixture perception as "olfactory targets" for game mechanic development, and present early design concepts for "Smelly Genes" and "Scenter." Finally, we discuss future directions and challenges for this new, interdisciplinary research topic.